Aflatoxicosis in a canine associated with consumption of contaminated food - case report - M.D. Furquim; F.F. Furquim; A.T. Nogueira; R. Zamboni; T.S. Alberti (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT Aflatoxins are mycotoxins produced by fungi that cause severe poisoning, mainly affecting the liver. Aflatoxicosis is rarely reported in dogs, but this species is extremely sensitive. The objective of this study was to report anatomopathological aspects of a case of aflatoxicosis in a male mongrel dog associated with ingestion of contaminated feed. The animal was treated at UNICRUZ Veterinary Hospital with a history of jaundice and apathy, which led to death within three days. At necropsy, marked jaundice of mucous membranes, subcutaneous tissue and intima of arteries, and a friable liver with accentuated lobular pattern were observed. Histopathological evaluation revealed intense vacuolization of hepatocytes, megalocytosis, fibrosis, proliferation of bile ducts and bilestasis. Samples of feed ingested by the animal were sent to Mycotoxicological Analysis Laboratory of UFSM, confirming high levels of aflatoxin. These poisonings occur due to ingestion of contaminated ingredients used in manufacture of dog food. The production of mycotoxins results from storage failures and poor quality of ingredients, which are often undetectable. The necropsy and histopathological findings, associated with clinical condition, were compatible with aflatoxicosis. The diagnosis was confirmed by assessing the aflatoxin levels in commercial food ingested by the animal.